Knowledge, Attitude and Practices towards the use of Intrauterine device among Women aged 15-49 years in Wakiso Health Centre IV Wakiso District. A Cross-sectional Study - Nangendo , Esther; Nakasolo , Sania (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study was to assess knowledge, attitude, and practices towards the utilization of IUDs among women aged 15-49 years in wakiso health center IV wakiso district. The specific objectives of the study were to assess the knowledge towards utilization of IUDs among women aged 15-49 years in wakiso health center IV, Wakiso district, attitude towards the utilization of contraceptives IUDs among women aged 15-49 years in wakiso health center IV wakiso district. Methodology: The descriptive cross-sectional study design was used with a simple random technique as a sampling technique. Data was collected using semi-structured questionnaires written in the English language and interviews. Results: From the study findings most (52%) respondents preferred to have four children, the majority of respondents, majority(80%) respondents have ever heard about IUDs, the majority(60%) obtained information about IUDs from the health facility, most (50%) respondents reported child spacing as the reason as to why they used IUDs, most (50%) respondents knew copper IUDs as a type of IUDs, the majority(70%) knew the site of administration of IUDs. Conclusion: Women had good knowledge and practices towards utilization of IUDs despite they had fair attitudes were noticed since most women felt uncomfortable due to side effects, would wish to change to other methods, and were not willing to advise their relatives or friends to use IUDs, Recommendation: The MOH, NGOs, and other stakes hold should train an adequate number of services providers and health extension workers in the safe removal of the risks or side effects associated with IUDs methods to mitigate the health-related problems.